Interventional Photothermal Therapy Enhanced Brachytherapy: A New Strategy to Fight Deep Pancreatic Cancer. Issue 5 (15th January 2019) - Zhang, Fengrong; Han, Xianlin; Hu, Yanyan; Wang, Shunhao; Liu, Shuang; Pan, Xueting; Wang, Hongyu; Ma, Junjie; Wang, Weiwei; Li, Shanshan; Wu, Qingyuan; Shen, Heyun; et al.
Abstract: Photothermal–radiotherapy (PT–RT) is an effective strategy for relieving hypoxia‐related radiotherapy resistance and inducing tumor‐specific cell apoptosis/necrosis. Nevertheless, limited tissue penetration of near‐infrared (NIR) laser and the serious side effects of high‐dose radiation severely hinder its applications for deep tumors. An interventional photothermal–brachytherapy (IPT–BT) technology is proposed here for the internal site‐specific treatment of deep tumors. This technology utilizes a kind of biodegradable honeycomb‐like gold nanoparticles (HGNs) acting as both internal photothermal agents and radiosensitizers. A high tumor inhibition rate of 96.6% is achieved in SW1990 orthotopic pancreatic tumor‐bearing mice by HGNs‐mediated IPT–BT synergistic therapy. Interestingly, this approach effectively causes double‐stranded DNA damage and improves the oxygen supply and the penetration of nanoparticles inside the tumor. Therefore, it is believed that this strategy may open up a new avenue for PT–RT synergistic therapy of deep malignant tumors and has a significant impact on the future clinical translation. Abstract : An interventional photothermal–brachytherapy (IPT–BT) based on honeycomb‐like gold for internal‐site‐specific treatment of deep pancreatic cancer is proposed, which can effectively cause double‐stranded DNA damage and improve the oxygen supply and the penetration of nanoparticles inside the tumor. This technology has a significant impact on future IPT–BT synergistic therapy of deep malignant tumors and clinical translation of IPTT.